Pola Komunikasi Antarbudaya Etnik Bajo dan Etnik Sikka Kelurahan Wolomarang Kabupaten Sikka - Rosina Mardiana Eman; Blajan Konradus; Yeheskial A Roen (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study analyzes communication patterns among the Bajo and Sikka ethnic groups in Wolomarang Village, Sikka Regency. The focus of this study is the patterns and dynamics of convergence and divergence in communication among the Bajo and Sikka ethnic groups in terms of social adaptation. Ethnographic methods were used because they enable researchers to understand the daily habits and interactions between the Bajo and Sikka ethnic communities that can be observed. Data were collected through participant observation, in-depth interviews, and documentation. The results of the study show that communication patterns are formed through continuous interactions in various areas of life, such as markets, residential environments, social activities, and religious activities. The patterns that emerge are generally open, adaptive, and accommodating, reflecting harmonious relationships despite cultural differences.  Convergence is evident through adjustments in speech patterns, language use, and social behavior to achieve mutual understanding, especially with the use of Indonesian as a lingua franca in public interactions. Divergence is seen when each ethnic group maintains its own language and distinctive communication characteristics. The Bajo ethnic group uses the Bajo language in internal interactions and exhibits a soft and religious style of speech, while the Sikka ethnic group uses the Sikka language with a firm and expressive communication style. Social adaptation is reflected in functional bilingualism and mixed family practices that combine values, languages, and traditions with mutual respect.